Resocialization Programme Evaluation of Street Children at Open House in Bandung City, Indonesia - Saripudin, Didin (EDUCARE, 2010)
ABSTRACT: This study aimed to evaluate resocialization programme of street children at open houses in Bandung city, Indonesia. Research design in this study was programme evaluation design using both quantitative and qualitative methods. This study used CIPP evaluation model suggested by D.L. Stufflebeam et al. (1971) by focusing on three of four components of CIPP evaluation model, which were input, process and product. Systematic random sampling was used to select respondents from 16 open houses in Bandung. The sample of this study was 522 people consisted of 36 administrators/managers, 132 facilitators and 354 street children. The questionnaires data was analyzed using descriptive analysis and inference such as frequency, percentage, min, ANOVA and multiple-regression using SPSS for Windows version 12. Interview and observation data were analyzed using R.C. Bogdan and S.K. Biklenâs analysis (1992). This study found that resocialization programme of street children at open houses in Bandung, from the aspect of input, process and product, generally in the medium level, still had some weaknesses that should be handled. Therefore, in the effort to reach the goal of street childrenâ resocialization programme at open houses, the improvement effort should be taken integratedly by all responsible ones. KEY WORDS: programme evaluation, resocialization, street children, open house in Bandung, and live normally as other children.About the Author: Didin Saripudin, M.Si. is a Lecturer at the Department of History Education, Faculty of Social Studies Education UPI (Indonesia University of Education), Jalan Dr. Setiabudhi No.229 Bandung 40154, West Java, Indonesia. He can be reached at: saripudinupi@yahoo.comHow to cite this article? Saripudin, Didin. (2010). âResocialization Programme Evaluation of Street Children at Open House in Bandung City, Indonesiaâ in EDUCARE: International Journal for Educational Studies, Vol.2(2) February, pp.185-196. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI in Bandung, West Java; and FKIP UMP in Purwokerto, Central Java, ISSN 1979-7877.Chronicle of the article: Accepted (December 11, 2009); Revised (January 11, 2010); and Published (February 17, 2010).